Adenovector-mediated hair cell regeneration is affected by promoter type - Praetorius, Mark; Hsu, Chi; Baker, Kim; Brough, Douglas E.; Plinkert, Peter K.; Staecker, Hinrich (Acta oto-laryngologica, 2010)
Conclusion: Replacement of vestibular hair cells induced by atoh1 driven by the tissue-specific GFAP promoter was significantly more efficient than use of the cBA or hCMV promoter. Objective: To test whether expression level, persistence, or selectivity from adenovirus vectors delivered in the inner ear can be altered by changing the adenovector backbone or by using different cellular and viral promoters. Materials and methods: Adenovector and promoter modifications were tested for differences in transgene expression in adult macular organs. The effect of using an E1/E3 deleted vector was compared to E1/E3/E4 deleted vectors. The effect of using viral and cellular promoters to modify transgene expression was tested in explanted adult mouse macular organs. Based on these results three different promoters were tested for efficacy of atonal gene. Results: Use of adenovectors containing human CMV, the hybrid cBA and ubiquitin promoters driving transgene expression resulted in different types of transgene expression. While several viral and cellular promoters provided broad cell type expression, expression driven by the GFAP promoter was limited to vestibular supporting cells, demonstrating the specificity of this promoter.
Gesehen am 05.05.2023